A Comparative Study of the Solvents Commonly Used to Detect Fibrin Stabilisation - Tyler, H. M (Thrombosis and Haemostasis, 1966)
The actions of 2% acetic acid, 1% monochloracetic acid and 8 M urea have been studied on fibrin of the “soluble” and “insoluble” types. The two acidic reagents have a much more rapid solubilising action than does 8 M urea, and are also more efficient in solubilising “partially stabilised” fibrin.Provided sufficient time is allowed for a fibrin or whole-blood clot to form, it seems unlikely that qualitative differences in the solubilising action of the three solvents will be found.For a clinical assessment of the stabilisation of blood-clot, examination can be made after 1 hr incubation of the clot in either of the acidic solvents. There is no apparent advantage in the commonly used prolonged incubations in 5 or 8 M urea.